2010
DOI: 10.2353/ajpath.2010.100569
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Overexpression of Anks6 Causes Polycystic Kidney Disease in Rats

Abstract: The PKD/Mhm(cy/؉) rat is a widely used animal model for the study of human autosomal dominant polycystic kidney disease, one of the most common genetic disorders, affecting one in 1000 individuals. We identified a new gene, Anks6, which is mutated (Anks6 (p.R823W) ) in PKD/Mhm(cy/؉) rats. The evidence for a causal link between Anks6 (p.R823W) and cystogenesis is still lacking, and the function of Anks6 is presently unknown. This study presents a novel transgenic rat model that overexpresses the mutated 2.8-kb … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…In the absence of published information regarding ANKS6 expression in the human fetal kidney, we performed immunohistochemistry in first-, second-, and third-trimester kidney tissues. Consistent with published animal data, 21 we found strong staining in S-shaped bodies and the Bowman's capsule but moderate staining in glomeruli of fetuses in the first and second trimesters of pregnancy. As the fetus develops, ANKS6 expression is restricted to the tubular epithelium and disappears from the glomeruli (Figure 2, B-E).…”
supporting
confidence: 92%
See 1 more Smart Citation
“…In the absence of published information regarding ANKS6 expression in the human fetal kidney, we performed immunohistochemistry in first-, second-, and third-trimester kidney tissues. Consistent with published animal data, 21 we found strong staining in S-shaped bodies and the Bowman's capsule but moderate staining in glomeruli of fetuses in the first and second trimesters of pregnancy. As the fetus develops, ANKS6 expression is restricted to the tubular epithelium and disappears from the glomeruli (Figure 2, B-E).…”
supporting
confidence: 92%
“…In addition, in neonatal PKD/Mhm(cy/+) rats, distinct Anks6 (p.R823W) mRNA expression has been found in the tubular epithelium and in podocytes. 21 Glomerular cysts have been reported in homozygous Nek8 knockout mice and in men harboring homozygous truncating NPHP3 mutations. 33,34 Moreover, the homozygous Pro209Leu mutation in TTC21B (encoding the cilia protein IFT139), which has previously been associated with isolated NPHP, was unexpectedly found to cause nephrotic syndrome/FSGS in seven families.…”
mentioning
confidence: 99%
“…4,24 However, in a newborn transgenic rat overexpressing the Anks6 R823W cDNA, cysts predominantly originate from the proximal tubules regardless of the expression of the transgene in other nephron segments including glomerular podocytes. 5 Similarly, ANKS6 is expressed in proximal tubules in control and ANKS6 I747N mice, whereas this nephron segment never develops cysts. Of interest, Pkd1 mouse models also show heterogeneity in the segments affected.…”
Section: Discussionmentioning
confidence: 98%
“…3 The PKD phenotype/genotype analysis of transgenic rats overexpressing Anks6 R823W showed that the R823W point mutation acts in a dominant negative manner. 5 Although the significance of Anks6 in PKD was demonstrated, its biological function and the molecular mechanisms leading to renal cyst formation are still largely unknown.…”
mentioning
confidence: 99%
“…thus, the abnormal expression of Samcystin may affect the normal structure and function of the proximal tubules. Neudecker et al developed transgenic rats with Anks6 (p.R823W) , a missense mutation (c>t) of the responsible PKD gene in the cy strain [37]. in this model, the expression of Anks6 is increased either in the immature or mature stages of kidney development, and the cysts are derived from the proximal tubules as in the Cy/+ rats of the spontaneous model, suggesting that gain-of-function by the mutated gene product may cause the disease.…”
Section: Spontaneous Hereditary Models Of Pkdmentioning
confidence: 99%